Life-threatening intrathyroidal parathyroid adenoma - Dogan, Ugur (Int J Clin Exp Med, 2015)
Acute primary hyperparathyroidism and parathyroid crisis are characterized by life-threatening hypercalcemia, a rare disorder. A 69-year-old female patient presented at our hospital’s neurology clinic with weakness, nausea, vomiting, depression, and hypercalcemia. Treatment of hypercalcemia resulted in no improvement in neurological symptoms, indicating resistance to treatment. Thyroid ultrasonography and parathyroid scintigraphy revealed hypoechoic nodules in the right lobe, pieces of nodules in the left lobe, and high serum calcium and parathyroid hormone levels. After provision of intensive medical treatment including hydration, diuresis, and bisphosphonate infusion resulted in only minimal decrease in the calcium level, urgent surgical treatment was performed. Frozen biopsy of the right intrathyroidal giant parathyroid adenoma in the right lobe confirmed initial diagnosis of primary hyperparathyroidism. Based on the biopsy findings, right parathyroidectomy and right total and left subtotal thyroidectomy were performed. Histopathologic examination revealed a parathyroid adenoma localized inside large thyroid nodules. Review of the findings resulted in diagnosis of intrathyroidal parathyroid adenoma. Symptoms of hypercalcemia improved rapidly during the postoperative period.